Five Step Total Synthesis of Lythranidine. (19th July 2021) - Magann, Nicholas L.; Blyth, Mitchell T.; Sherburn, Michael S.
Abstract: A concise synthesis of the alkaloid lythranidine is reported. The strategy exploits the target's local C2 symmetry by adopting a two directional synthetic approach, first in an acyclic environment, then in a cyclic system and finally in a bridged macrocyclic domain. The latter phase of the synthesis, which installs all four stereocenters, involves a thermodynamically controlled, twofold intermolecular/transannular aza‐Michael addition and a twofold hydride reduction. The synthesis is one third of the length of the most step‐economic previous approach, providing access to gram quantities of the natural product. The broad‐spectrum nature of the synthesis is demonstrated through the preparation of three diastereomeric analogues of the natural product. Abstract : Design and implementation of a symmetry‐focused, two‐directional strategy leads to an extraordinarily short synthesis of the macrocyclic metacyclophane natural product lythranidine and most of its diastereomers.